2021
DOI: 10.3390/plants10020361
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzocyclooctadiene Lignans in Plant Parts and Fermented Beverages of Schisandra chinensis

Abstract: The fruit of Schisandra chinensis, Omija, is a well-known traditional medicine used as an anti-tussive and anti-diarrhea agent, with various biological activities derived from the dibenzocyclooctadiene-type lignans. A high-pressure liquid chromatography-diode array detector (HPLC-DAD) method was used to determine seven lignans (schisandrol A and B, tigloylgomisin H, angeloylgomisin H, schisandrin A, B, and C) in the different plant parts and beverages of the fruit of S. chinensis grown in Korea. The contents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The authors concluded that the type of sugar also plays a part in the fermentation outcome of lignans. 26 Pickling is a different form of natural fermentation of fruits and vegetables in acidic or salt solutions. A study focused on the effect of pickling on the lignan content in shallots, celery, green Chinese mustard, and long beans.…”
Section: Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the type of sugar also plays a part in the fermentation outcome of lignans. 26 Pickling is a different form of natural fermentation of fruits and vegetables in acidic or salt solutions. A study focused on the effect of pickling on the lignan content in shallots, celery, green Chinese mustard, and long beans.…”
Section: Acsmentioning
confidence: 99%
“…NADS, such as sugars, in the solid form, can improve the solubility of nonwater-soluble bioactive compounds such as lignans. The authors concluded that the type of sugar also plays a part in the fermentation outcome of lignans …”
Section: Stability Of Lignansmentioning
confidence: 99%
“…As a result, contents of lignan were the highest in seed, followed by fruit, flower, leaf, pup, and stem. Lignan content increased proportionally to fermentation period, and the Omija beverage fermented with oligosaccharide/white sugar had the highest contents of lignan compared to beverages fermented with other sugars [6].…”
mentioning
confidence: 96%
“…By isolating and characterizing the compounds in extracts, it helps to elucidate the pharmacological activities from the extract and explains the biochemical metabolism of compounds inside plants and herbs. In this Special Issue, thirteen research articles [1][2][3][4][5][6][7][8][9][10][11][12][13] and two reviews [14,15] focusing on isolation and analysis of compounds from plant extracts have been published. This Special Issue of Plants covers a broad range of recent findings of isolation, profiling, analysis of compounds from herbal and plant extracts, quality control, and standardization of processing extracts with characterized compounds.…”
mentioning
confidence: 99%
“…Over the years, attempts have been made to characterize the origin, fate and function of this unique compound [2,3]. Initially discovered in a fungal contaminant of rye grain, EGT is present in some anaerobic [4] and aerobic [5] micro-organisms, as well as plants [6], and was later found to be highly concentrated in the cells [7], organs and tissues [8] of most animals and humans.…”
mentioning
confidence: 99%